Who, What, Where: an analysis of private sector family planning provision in 57 low‐ and middle‐income countries. Issue 12 (28th September 2015) - Campbell, Oona M. R.; Benova, Lenka; Macleod, David; Goodman, Catherine; Footman, Katharine; Pereira, Audrey L.; Lynch, Caroline A.
Abstract: Objective: Family planning service delivery has been neglected; rigorous analyses of the patterns of contraceptive provision are needed to inform strategies to address this neglect. Methods: We used 57 nationally representative Demographic and Health Surveys in low‐ and middle‐income countries (2000–2013) in four geographic regions to estimate need for contraceptive services, and examined the sector of provision, by women's socio‐economic position. We also assessed method mix and whether women were informed of side effects. Results: Modern contraceptive use among women in need was lowest in sub‐Saharan Africa (39%), with other regions ranging from 64% to 72%. The private sector share of the family planning market was 37–39% of users across the regions and 37% overall (median across countries: 41%). Private sector users accessed medical providers (range across regions: 30–60%, overall mean: 54% and median across countries 23%), specialised drug sellers (range across regions: 31–52%, overall mean: 36% and median across countries: 43%) and retailers (range across regions: 3–14%, overall mean: 6% and median across countries: 6%). Private retailers played a more important role in sub‐Saharan Africa (14%) than in other regions (3–5%). NGOs and FBOs served a small percentage. Privileged women (richest wealth quintile, urban residents or secondary‐/tertiary‐level education) used private sector services more than the less privileged. Contraceptive method types with higher requirements (medical skills) for provision were less likely to be acquired from the private sector, while short‐acting methods/injectables were more likely. The percentages of women informed of side effects varied by method and provider subtype, but within subtypes were higher among public than private medical providers for four of five methods assessed. Conclusion: Given the importance of private sector providers, we need to understand why women choose their services, what quality services the private sector provides, and how it can be improved. However, when prioritising one of the two sectors (public vs . private), it is critical to consider the potential impact on contraceptive prevalence and equity of met need.